Radially symmetric scalar field solutions in the presence of cuscuton term - D. Bazeia; M. A. Marques; R. Menezes; M. Paganelly (European Physical Journal C: Particles and Fields)
Abstract In this work, we investigate radially symmetric solutions in arbitrary dimensions in scalar field models in the presence of the cuscuton term. We introduce a first-order formalism compatible with the equation of motion which supports field configurations engendering minimum energy and show that the cuscuton term does not induce instabilities in the solutions. To illustrate the general results, we study two distinct classes of models and present analytical solutions and the corresponding energy densities.